Online resale of luxury goods: The new luxury - Gomes, Mariana Helena Almeida Ferreira (2021)
The purchase of pre-owned luxury goods is now a worldwide trend. The search for sustainable consumption and the desire for luxury products have made this market grow exponentially in recent years. The present research aims to analyse the second-hand luxury market in Portugal, focusing on the online. This study aims to answer the following questions: (1) What are the main reasons for purchasing second-hand luxury products, mainly through digital? (2) Is the first-hand luxury consumer a second-hand luxury consumer? And (3) How is the shopping experience? Positive or negative? For that, a qualitative method that counts with four interviews to Portuguese luxury resale companies, and a quantitative method with an online survey distributed to 241 second-hand luxury consumers living in Portugal was done. The research results reveal that (1) The main reasons for purchasing second-hand luxury in general and online in Portugal are: the product being cheaper, access to rare products, search for a more responsible consumption, the ease of access to a greater variety of products, compare prices, read testimonials from other consumers, have access to promotions and not having to leave home to make a purchase; (2) The consumer who buys second-hand luxury also buys first hand luxury products; and (3) The experience of buying second-hand luxury in Portugal is positive.